2005
DOI: 10.1530/rep.1.00642
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibroblast growth factor-8 and regulation of cognate receptors, fibroblast growth factor receptor-3c and -4, in bovine antral follicles

Abstract: Paracrine cell signaling is believed to be important for ovarian follicle development, and a role for some members of the fibroblast growth factor (FGF) family has been suggested. In the present study, we tested the hypothesis that FGF-8 and its cognate receptors (FGFR3c and FGFR4) are expressed in bovine antral follicles. RT-PCR was used to analyze bovine Fgf8, Fgfr3c and Fgfr4 mRNA levels in oocytes, and granulosa and theca cells. Fgf8 expression was detected in oocytes and in granulosa and theca cells; this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 32 publications
2
57
0
3
Order By: Relevance
“…FGF8 is expressed in antral follicles in rat and cow. It may also play a role in the development of ovarian and breast tumors (Valve et al 1997, Daphna-Iken et al 1998, Zammit et al 2002, Buratini et al 2005. STC1 was originally shown to have high expression levels in the ovary (Varghese et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…FGF8 is expressed in antral follicles in rat and cow. It may also play a role in the development of ovarian and breast tumors (Valve et al 1997, Daphna-Iken et al 1998, Zammit et al 2002, Buratini et al 2005. STC1 was originally shown to have high expression levels in the ovary (Varghese et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This expression profile suggests that FGF8 plays a paracrine role, signalling between the oocyte and follicular somatic cells during the final stages of follicular maturation (Valve et al 1997). However, it has been reported that FGF8 is expressed in oocytes, granulosa cells and theca cells within bovine antral follicles (Buratini et al 2005), suggesting an autocrine/paracrine mode of signalling. CTGF is a matrix-associated heparin binding protein that is regulated by gonadotrophins and is expressed in antral follicles and corpus lutea in the rat (Harlow et al 2007).…”
Section: Regulation Of Ovarian Function By Neurotrophinsmentioning
confidence: 96%
“…These represent mature dominant growing, static and regressing follicles respectively (Price et al 1995). Cross-contamination of theca and granulosa cells was tested by detection of mRNA encoding cytochromes P450 aromatase (Cyp19) and 17a-hydroxylase (Cyp17) in each sample by PCR (Buratini et al 2005). Only granulosa cell samples negative for Cyp17, and only thecal samples negative for Cyp19 amplicons were included in the analysis (number of follicles used given above).…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Briefly, for both theca and granulosa cells, total RNA (1 mg) was incubated with DNAse I (Invitrogen) and reverse transcribed with SuperScript II (Invitrogen) and oligo-d(T) primer (Buratini et al 2005). An aliquot (0.4 ml) of the cDNA template was amplified by PCR using 0.2 ml (2.5 U) Taq Polymerase (Amersham Pharmacia Biotech, Inc., Oakville, ON, Canada) in a 20 ml PCR buffer (Amersham Pharmacia Biotech) containing 0.1 mM dNTP mix, and 0.2 mM specific primers (Cao et al 2004).…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%